No savings, just pain: School closures and “reform” in Puerto Rico (Alternautas, 2022)
Some of the very first austerity measures announced or foreshadowed by the FOMB targeted Puerto Rico’s public schools and universities[14], and closures picked up pace when governor Roselló, who won the election in 2016 with a platform that included the argument that the 72 billion debt was actually payable, named Julia Keleher his secretary of education. By then, Keleher had been formally connected with educational reform in Puerto Rico, in one way or another, for nine years and two administrations, Roselló’s being the third[15]. Under her now formalized leadership, hundreds of schools were closed, and a comprehensive educational reform was passed and signed into law, shortly and swiftly after the island was hit by hurricane Maria in 2017.